2008
DOI: 10.3748/wjg.14.899
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of some vitamins against the toxic action of ethanol on liver regeneration induced by partial hepatectomy in rats

Abstract: Vitamins C and E protect against liver injury and dysfunction, attenuate lipid peroxidation, and thus appear to be significantly more effective than vitamin A against ethanol-mediated toxic effects during liver regeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Bradford reported that activation of CYP2E1 is important for ethanol-induced DNA damage in the liver and ethanol-related hepatocellular carcinogenesis. ( 57 ) If an injury involves other organelles, such as mitochondria, soluble enzymes, such as AST and ALT, will also be released into the blood, indicating that PH causes cellular damage, ( 11 , 58 ) and reduces residual liver function. ( 59 ) ALT is predominantly found in the liver, whereas AST is found in many organs including the liver, cardiac muscle, skeletal muscle and erythrocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bradford reported that activation of CYP2E1 is important for ethanol-induced DNA damage in the liver and ethanol-related hepatocellular carcinogenesis. ( 57 ) If an injury involves other organelles, such as mitochondria, soluble enzymes, such as AST and ALT, will also be released into the blood, indicating that PH causes cellular damage, ( 11 , 58 ) and reduces residual liver function. ( 59 ) ALT is predominantly found in the liver, whereas AST is found in many organs including the liver, cardiac muscle, skeletal muscle and erythrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatic regeneration was determined by the calculation of liver weight regeneration and total DNA concentration. ( 11 ) Each post-PH liver remnant was weighed at the time of death. For each rat, the weight of the remnant liver was normalized to the weight of the rat’s entire liver at the time of PH and expressed as the percentage of the rat’s final body weight according to the following formula: (weight of remnant liver/final body weight) × 100.…”
Section: Methodsmentioning
confidence: 99%
“…Parra-Vizuet et al[ 24 ] reported a diminution in the serum levels of AST and ALT 24 h after the administration of a unique dose of alcohol of 1.5 g/kg. On the other hand, Morales-González et al[ 15 ] and Ramírez-Farías et al[ 25 ] reported an increase in the serum levels of the transaminases (ALT, AST, LDH, GDH and OTC) 7 d after the administration of ethanol. Similarly, Morales-González et al[ 26 ] reported a diminution in the activity of transaminase enzymes in hepatic tissue 24 h after ethanol administration (5 g/kg).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Trejo-Solis et al [ 15 ] found a diminution in PH-induced liver regeneration on the administration of vitamin E, the authors concluding that treatment with vitamin E probably could promote an anticipated termination of the preparative events leading to the replicative phase of pH-induced liver regeneration. Ramírez-Farías et al [ 16 ] reported that administration of ethanol increases lipid peroxidation levels in rats that had been submitted to PH, giving rise to the inhibition of liver regeneration, while the administration of vitamin E diminished the levels of the lipid peroxidation that produced ethanol, favoring PH-induced liver regeneration.…”
Section: Liver Regenerationmentioning
confidence: 99%